Macromolecular Characterization of Swordfish Oocytes by FTIR Imaging Spectroscopy - Carnevali, Oliana (Sci Rep, 2019)
During folliculogenesis, primary oocytes of teleosts grow by several orders of magnitude by-self synthesizing proteins and mRNA, or sequestering from blood specific macromolecular components, such as fatty acids and vitellogenin. All these materials are stored into cortical alveoli, yolk globules or oil droplets during oocyte development. The proper synthesis, storage and displacement of these macromolecular components inside the oocyte play a key role for a successful fertilization process and for the subsequently correct embryo development. In this study, for the first time, the FTIR Imaging (FTIRI) spectroscopy has been applied to characterize the chemical building blocks of several cellular components of swordfish oocytes at different developmental stages. In particular, the spectral features of previtellogenic (PV), vitellogenic (VTG), mature (M) and atretic (A) follicles as well as and of cortical alveoli (CA), yolk vesicles (YV), oil droplets (OD) and Zona Radiata (ZR) have been outlined, providing new insights in terms of composition and topographical distribution of macromolecules of biological interest such as lipids, proteins, carbohydrates and phosphates. The macromolecular characterization of swordfish oocytes at different developmental stages represents a starting point and a useful tool for the assessment of swordfish egg quality caught in different conditions, such as periods of the year or different fishing area.